An uneven touch to the picture of Inter-Church relations in the mid-1930s. A letter from metropolitan of Moscow Sergiy (Stragorodsky) to Patriarch of Constantinople Veniamin (Psomas) on the occasion of the meeting of Russian foreign hierarchs chaired by Patriarch of Serbia Barnabas (Rosic) - Aleksandr Mazyrin; Andrey Kostryukov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The published letter was written by the Deputy Patriarchal Locum Tenens Metropolitan Sergius (Stragorodsky) to the Patriarch of Constantinople Benjamin (Psaomas). The occasion was a meeting of the heads of the main movements of the Russian Church abroad in 1935, chaired by Patriarch Barnabas of Serbia. As a result of the negotiations, the Russian Church Abroad, the North American Metropolia and the Western European Exarchate restored communication among themselves. This caused discontent of Metropolitan Sergius (Stragorodsky), who hoped to subordinate the entire Russian church abroad. Attempts to influence Patriarch Barnabas were unsuccessful. In this regard, the Deputy Patriarchal Locum Tenens appealed to Patriarch Benjamin of Constantinople. Russian Russian Orthodox Church In his letter, the Metropolitan pointed out that the Serbian Church wants to create a kind of "double" of the Russian Church on the basis of the Russian Church Abroad, and then at the Pan–Orthodox Council to achieve the necessary solution - the introduction of second marriage for the clergy.The appeal to the Fanar looks strange for several reasons. Firstly, the Patriarchate of Constantinople openly supported the Renovationist schism in those years and, almost at the same time, uncanonically, without asking the opinion of the Moscow Patriarchate, transferred the Latvian Church to its jurisdiction. Secondly, the Serbian Church, and especially the Russian Church Abroad, which was under its patronage, were against non-canonical innovations, and it was naive to assume that they would promote the second marriage of the clergy. The published letter of Metropolitan Sergius had no consequences. Later, when the situation of the Russian Church improved, the parties tried not to recall this letter, as well as other polemical messages.